Microgel-stabilized liquid crystal emulsions enable an analyte-induced ordering transition. Issue 50 (6th June 2019) - Dan, Abhijit; Agnihotri, Priyanshi; Brugnoni, Monia; Siemes, Eric; Wöll, Dominik; Crassous, Jérôme J.; Richtering, Walter
Abstract : Microgels enable reversible stabilization of liquid crystal (LC) emulsions in ways that facilitate analysis of LC droplets that undergo an analyte-triggered conformational transition. Abstract : We develop a new strategy that involves the formation of microgel (MG) decorated liquid crystal (LC) droplets, which show remarkable stability. This system facilitates the analysis of the LC droplets that undergo an analyte-triggered conformational transition, thus optimizing the quantitation of aqueous analytes.